2018
DOI: 10.1016/j.ejvs.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

18 F-FDG Uptake on PET/CT in Symptomatic versus Asymptomatic Carotid Disease: a Meta-Analysis

Abstract: IntroductionThe role of positron emission tomography (PET)/computed tomography (CT) in the determination of inflammation in arterial disease is not well defined. This can provide information about arterial wall inflammation in atherosclerotic disease, and may give insight into plaque stability. The aim of this review was to perform a meta-analysis of PET/CT with 18F-FDG (fluorodeoxyglucose) uptake in symptomatic and asymptomatic carotid artery disease.MethodsThis was a systematic review, following PRISMA guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…With follow-up, several FDG-avid lesions were abrogated in patients who achieved smoking cessation. Beyond our four case studies, similar findings were observed in meta-analysis by Chowdhury et al showing a difference in radionucleotide uptake in symptomatic versus asymptomatic carotid disease [4]. In the abdominal aorta, Higashigawa et al demonstrated that dissected aortic walls had higher levels of FDG uptake [9].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…With follow-up, several FDG-avid lesions were abrogated in patients who achieved smoking cessation. Beyond our four case studies, similar findings were observed in meta-analysis by Chowdhury et al showing a difference in radionucleotide uptake in symptomatic versus asymptomatic carotid disease [4]. In the abdominal aorta, Higashigawa et al demonstrated that dissected aortic walls had higher levels of FDG uptake [9].…”
Section: Discussionsupporting
confidence: 90%
“…Glucose is commonly taken up by metabolically active cells. In the case of atherogenesis, macrophages that are working hard in the intima increase expression of glucose transporters [4]. Lipid-laden macrophages may consequently accumulate in inflammatory atherosclerotic plaques.…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular imaging techniques have been proposed to localize and characterize atheroma (62), including radiolabeled autologous LDLc (63), radiolabeled antibodies recognizing oxidized LDLc (64), radiolabeled somatostatin receptor antagonists (to image somatostatin receptors expressed by inflamed atheroma) (65), radiotracers localizing in hypoxic atheroma (66), 18 F-FDG (67) to identify focal vascular inflammation, and recently, imaging with 18 F-fluoride (68) to identify active calcification. Although 18 F-FDG localizes in the carotid arteries of patients with symptomatic carotid disease, it remains unclear whether 18 F-FDG coronary arterial uptake correlates with coronary events (69). In a direct comparison of 18 F-FDG to 18 F-sodium fluoride in patients with myocardial infarction and stable angina, ''NaF showed substantially higher uptake in the culprit plaque (70).''…”
Section: Potential Role Of Molecular Imagingmentioning
confidence: 99%
“…The goal of the imaging technique is to detect carotid plaques that are at high risk of rupture and therefore carry high risk of stroke. 18 F-FDG PET for the detection of unstable plaques is not in clinical use [8], partly due to lack of feasible PET protocols and consensus regarding imaging procedure, method for 18 F-FDG uptake quantification and assessment of stroke risk, although several recommendations exist [9, 10]. PET is an imaging modality with limited anatomical information, and it might therefore be challenging to define the vessel-segment-of-interest.…”
Section: Introductionmentioning
confidence: 99%